Sustainable Approaches to Selective Conversion of Cellulose Into 5-Hydroxymethylfurfural Promoted by Heterogeneous Acid Catalysts: A Review - Yao, Yuanyong; Chen, Shixue; Zhang, Meng (Frontiers in Chemistry, 2022)
5‑(Hydroxymethyl) furfural as a triply catalytic product is a high value-added refining chemical in industry production. 5-HMF as biomass feedstock enables to be transformed into other high valuable industrial compounds, such as 2,5-furandicarboxylic acid (FDCA), 5-hydroxymethyl-2-furancarboxylic acid (HMFCA), 5-Formyl-2-furancarboxylic acid (FFCA), 2,5-diformylfuran (DFF), 2, 5-bis (aminomethyl) furan (BAMF) and 2,5-Dimethyl furan (DMF) and so on. Hence, to the conversion of biomass into 5-HMF has been paid much more attention by chemists. In this review, there are some latest works about conversion of cellulose to 5-HMF have been introduced systematically. To the best knowledge, catalysts are effective promoters for catalytic biomass conversions. Solid acids as heterogeneous catalysts have been widely applied to the conversion of cellulose into 5-HMF. Therefore, some novel solid acids with Bonsted and / or Lewis acidic sites, such as sulfonated solid acids, carbon-based acids and zeolite particles, respectively employed to biomass conversions are listed.